Findings of Paediatric Upper Gastrointestinal Endoscopy at a Tertiary Care Centre - Thapa, Surya Bahadur; Sharma, Arun Kumar (Journal of Nepal Paediatric Society, 2016)
Introduction: Endoscopy is an important diagnostic tool for gastrointestinal disorders in children. Practitioners still debate the need and utility of endoscopy in children and this important evaluation is potentially underutilized. There is a paucity of paediatric endoscopy data in Nepal. This report describes an initial three-year experience on profile of upper gastrointestinal endoscopy at Tribhuvan University Teaching Hospital (TUTH). Material and Methods: This retrospective study was conducted by reviewing hospital records for children undergoing endoscopy for various indications at TUTH during November 2011 to October 2014 (3 years). Results: We performed 362 endoscopies during this period. Mean age of patients was 9.49 years (range 2 months to 18 years) and 199 (54.9%) patients were under 10 years of age. Common indications were upper gastrointestinal bleeding (27.6%), recurrent abdominal pain (26.2%), acute abdominal pain (24.6%), recurrent vomiting (5.2%), and caustic ingestion (3.6%). An abnormality was detected in 159 (42.2%) patients. Varices (16.6%), gastritis/duodenitis (14.9%), ulcer (3.3%), oesophagitis (1.9%) were common diagnoses. Etiology of upper gastrointestinal bleed was identified in 65% of patients. Majority of patients with recurrent abdominal pain had negative results (80%). Failure to thrive constituted a very small proportion of children (0.2%) evaluated. All children received sedation/ analgesia and tolerated the procedure well. Conclusion: Paediatric upper gastrointestinal endoscopy can be safely performed across wide age range with proper sedation/ analgesia. Endoscopic diagnosis may improve management and children requiring such evaluation should be timely referred. Paediatricians should be encouraged to refer patients with growth failure early to ensure proper management. J Nepal Paediatr Soc 2015;35(2):123-128